Digital Transformation of Accounting Practices and Behavior During COVID-19: MENA Evidence - Khalil Feghali; Joelle Matta; Samir Moussa (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - What are the impacts of digital transformation of accounting practices and behavior following the COVID-19 pandemic? Motivation - The outbreak of the health crisis linked to COVID-19 pandemic has turned massively the companies to adopt digital platforms for accounting function in order to keep concurrent pace with the emergent crisis at all levels (Begum, 2019). Many tools have emerged in terms of accounting procedures such as Artificial Intelligence, Big Data, e-accounting, and its adoption impacted accountant's behavior (Damerji & Salimi, 2021). Key stakeholders of this study include accountants and companies. Idea - We examine the impact of level of digitalization and changes caused by COVID-19 on accountant's behavior throughout multiple items. The independent variables utilized were, firm size, sector and position within companies. Data - We surveyed and analyzed a sample of 568 accountants operating in private companies in the MENA region, between February and April 2021, using SPSS software. Tools - A quantitative approach is adopted through a questionnaire-based survey. A sample of accountants in the MENA region was surveyed. Findings - Results show that changes caused by COVID-19 have a negative effect on accountant's behavior in terms of attitude, effort, expectancy, and adaptation. Otherwise, the level of digitalization, position occupied by the accountant and firm size have a positive effect on accountant's behavior in MENA region. Contribution - This paper contributes to literature by finding a concept foundation in order to help accounting profession in MENA region to digital transformation many processes. This paper helps accountants to adapt to changes engendered by COVID-19.
Keywords: M40; M41; O30; O31; O32; O33; 650; digital transformation; accounting practices; behavior; COVID-19